2007
DOI: 10.1002/nur.20178
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of quality of life in old age: A cross‐validation study

Abstract: A replication study was undertaken to validate a model of quality of life (QOL) generated in an earlier study on a random sample of 202 older adults. Pathways found to be significant were retested using QOL data from a convenience sample of 420 older adults. Using path analysis, we found that financial resources, health, and meaning in life directly and positively influenced QOL. Health, emotional support, and the physical environment indirectly affected QOL through purpose in life. All but one pathway were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
76
1
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(93 citation statements)
references
References 49 publications
9
76
1
7
Order By: Relevance
“…Again, this makes conceptual sense, as a smaller percentage of the LBC1936 lived alone and so this factor may have more impact in early old age. This is in keeping with previous studies which have suggested a crucial role for social relationships and support in predicting QoL [21].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Again, this makes conceptual sense, as a smaller percentage of the LBC1936 lived alone and so this factor may have more impact in early old age. This is in keeping with previous studies which have suggested a crucial role for social relationships and support in predicting QoL [21].…”
Section: Discussionsupporting
confidence: 93%
“…This therefore restricts the applicability of our models to the general population. However, other studies of the determinants of quality of life have also suggested that models may be population-specific [21]. Another potential limitation is the timing of our measures: the measurement of QoL and personality were not exactly concurrent with each other or the measurement of old age cognition and physical health in the LBC1921, although this was rectified in the LBC1936.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Replication studies are rarely undertaken to further validate models of QoL, yet they enable researchers to disentangle sample-dependent findings (Low and Molzahn 2007). In this study, there were cultural differences noted in the patterns found in the BREF measurement model.…”
Section: Discussionmentioning
confidence: 83%
“…Differences in QoL among Canadians and Americans are explained by age, gender, education, income, marital status and country of residence [28]. Low G. et al [29] examined whether risk factors were associated directly and positively with QoL.…”
mentioning
confidence: 99%